Vigna radiata : production, cultivation and uses - Bech, Martin L. (New York : Nova Science, 2021)
"This book contains ten chapters that each provide a different perspective on Vigna radiata, a species of plant in the legume family also known as green gram or mung bean that is used as an ingredient in savory and sweet dishes. Chapters One and Two discuss various potential modern approaches to improve green gram production, including prospects for genetic improvement. Chapter Three focuses on the impact of drought stress on green gram production and various approaches to manage the severity of drought stress. Chapter Four describes the application of Plant Growth Promoting Bacteria (PGPB) on green gram production, while Chapter Five reviews the nutritional composition and health promoting effects of green gram. Chapter Six discusses approaches to abiotic stress management in green gram, whereas Chapter Seven deals with improving soil fertility status for green gram production, and Chapter Eight discusses advanced strategies in disease management of green gram. Chapter Nine proposes various breeding strategies for enhancing or creating new traits in green gram, such as early maturity, long pods, and more seeds. Finally, Chapter Ten focuses on improving farmers' livelihood by extending marketing strategies to solve problems such as unstable price, lack of marketing information, and inadequate storage facilities"--
Includes bibliographical references and index.
Issued also in electronic format.
Keywords: Mung bean